KOMPOSISI SEMUT (HYMENOPTERA: FORMICIDAE) PADA PERTANAMAN KAKAO (Theobroma cacao L.) DI DESA MUNTEI KECAMATAN SIBERUT SELATAN KABUPATEN KEPULAUAN MENTAWAI - Tatebburuk, Noviana - (Pendidikan Biologi, 2014)
study about composition of ants in cacao plantation (Theobroma cacao L.) and forest edge was conducted from August until Septembert 2014 in Muntei Village, South Siberut, Mentawai Island. The ant was collected by using hand collecting method. A total of 17 species of ant that belonging to 14 genera, 8 tribe, and 5 subfamilies of ants was collected. Formicinae was found as the subfamily with the highest number of species (6 species) followed by Ponerinae (5 species) and Dolichoderinae (4 species), meanwhile Myrmicinae and Ectatomminae were found one species respectively. The highest of relative density was showed by Dolichoderus thoracicus (63,32%) at cacao plantation and the lowest relative density was found in Polyrachis abdominalis (0,07%) at forest edge.